Fundamental investigations on interrupted machining of challenging materials with MQL - Alammari, Youssef (Technische Universität Dortmund, 2024)
Challenges associated with sustainable manufacturing are investigated by exploring new approaches to optimize resources utilization during machining. The focus is on understanding fundamental tribological aspects, particularly during chip formation, with an emphasis on interrupted machining using minimum quantity lubrication (MQL). Investigations into difficult-to-cut materials, such as austenitic stainless steel and Inconel 718, reveal significant reductions in chip-tool contact during initial period of chip formation (IPCF). Thermal modeling establishes correlations between a finite cutting distance of IPCF and a transition temperatures contributing to a better understanding of the process. Practical case studies employing peck drilling and vibration-assisted drilling demonstrate both the potentials and challenges associated with introducing interruptions in continuous machining operations.
Schriftenreihe des ISF;110
Keywords: Interrupted machining; Minimum quantity lubrication; Initial period of chip formation; Vibration assisted drilling; 620; 670; Fertigung; Minimalmengenschmierung; Spanbildung; Tribosystem; Spanende Bearbeitung